Sostenibilidad social en el sector agroindustrial del estado Trujillo–Venezuela. Un constructo relevante para el desarrollo (2019)
This paper was to analyze the social sustainability of the Agroindustry of the Trujillo-Venezuela state. Realism was used as an ontological reference, consistent with the inductive empirical epistemological approach of quantitative studies, with a field design, not experimental and cross. The population was constituted by twentytwo (22) companies, whose administrators were given a semistructured questionnaire with 17 items. The processing of the information was done through descriptive statistics. The results show that these companies have a medium level of social sustainability, influenced by the degree of competitiveness of the five dimensions that make it up.